Analisis Kesalahan Bahasa Arab dalam Penulisan Karya Ilmiah: (Studi Kasus Mahasiswa Program Studi Pendidikan Bahasa Arab Universitas KH. A. Wahab Hasbullah Jombang) - Maulidiyah, Lailia; Shofiyani, Amrini (Qismul Arab: Journal of Arabic Education, 2023)
The writing of this article departs from the problem of some students who have errors in applying the nahwu-shorof rule in writing perfect sentences in Arabic articles that have compatibility between nahwu-shorof or the selection of appropriate sentences. This qualitative description research analyzes errors in the application of Arabic rules in PBA UNWAHA student articles. Through observations of 5 random Arabic articles of PBA UNWAHA students from across years, researchers can approach error analysis by identifying errors, classifying errors, describing errors, and analyzing the factors that cause errors based on linguistic phenomena that appear in Arabic articles of PBA UNWAHA students. The results of this study showed that overall, there were 60 errors from the 5 articles. The data showed that of the 5 articles, 36.7% experienced errors in choosing appropriate sentences, 53.3% experienced errors in compatibility between mudzakkar-muannats, and the remaining 10% experienced errors in the aspect of i'rob. The factors causing the error are linguistic and social. To avoid language errors, students must focus more on Arabic rules, be careful in the translation and selection of appropriate sentences, and apply sentence analysis before publishing articles to apply the theory and practice of applying Arabic rules.